Assistance for Florida's Rural Communities: The Rural Economic Development Initiative - Hank Cothran; David Mulkey; Mary Helen Blakeslee (EDIS)
The Rural Economic Development Initiative (REDI) was established to better serve Florida's rural communities by providing a more focused and coordinated effort among state and regional agencies that provide programs and services for rural areas. REDI is housed in the Governor's Office of Tourism, Trade, and Economic Development (OTTED) where it coordinates the efforts of state and regional agencies working to assist qualified communities. This document specifies the criteria for eligibility for assistance, notes the participating agencies, describes the duties and responsibilities of REDI, and provides contact information. This is EDIS document FE426, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published August 2003.